Learning System of Islamic Religious Education - Lukman, Aulia (IAI Al-Mawaddah Warrahmah Kolaka, 2022)
Humans as creatures created by Allah SWT have been given extraordinary potential in the form of perfect physical and spiritual. Human perfection is more complete and complete with the addition of reason. With this potential, humans develop themselves to utilize all these potentials until they reach the degree of human perfection. However, human perfection can be lowered in degree, even lower than the level of animals if humans are not able to maintain that perfection. In order to keep the degree of humans not lower than the degrees of animals, humans must understand, maintain and develop their nature through education. Armed with this potential, humans are given the freedom to determine their life path, whether to choose the path of goodness or choose the path of evil. Later in front of Allah, for this choice, humans will be held accountable. However, for all of God's mercy and love for humans, he was not allowed to just choose his life path, but Allah sent down the Qur'an as a guide and source of knowledge as a provision to achieve happiness in this world and the hereafter. The ultimate goal of man in Islam is what can also be called the ultimate goal of Islamic education.